Culture Impacts the Neural Response to Perceiving Outgroups Among Black and White Faces - Hughes, Colleen; Babbitt, Laura G.; Krendl, Anne C. (Frontiers in Human Neuroscience, 2019)
Outgroup members (e.g., individuals whose racial identity differs from perceivers’) are stigmatized in Eastern and Western cultures. However, it remains an open question how specific cultural influences affect stigmatization. In this study, we assessed whether cultural learning (i.e., social information acquired from the people in one’s environment) associated with Chinese individuals’ relocation to the United States differentiated the response to multiple outgroups. Two types of cultural learning predict diverging responses to outgroups – awareness of stereotypes about different racial outgroups is associated with increased negative affect and cognitive control towards the stereotyped outgroup. Conversely, intergroup contact attenuates those responses, and does so to a greater extent for individuals from Western cultures. As Chinese-Americans would have had more opportunities to have contact with both White and Black individuals (relative to the Chinese participants), we explored their responses to outgroups as well. Because the neural regions associated with stereotyping and intergroup contact have been well-characterized, we used neuroimaging to disentangle these possibilities. Eighteen White American, 18 Chinese-American, and 17 Chinese participants – who had relocated to the United States less than one year prior – viewed images of Black and White individuals while undergoing functional magnetic resonance imaging (fMRI). Participants also completed measures of awareness of cultural stereotypes in the United States about Black and White individuals, implicit bias, and experiences with White and Black individuals. Behaviorally, White American and Chinese-American participants had more intergroup contact with either race than did Chinese participants, but there was no effect of participant group on stereotype knowledge or implicit bias. When viewing faces of White (as compared to Black) individuals while undergoing fMRI, White American (relative to Chinese) participants had attenuated activation in regions of the brain associated with cognitive control, including the right dorsolateral prefrontal cortex, dorsal striatum, and ventrolateral prefrontal cortex. Chinese-Americans’ neural response to either race did not differ from White American or Chinese participants. Taken together, outgroup biases seemed to emerge in a culturally-dependent way based on variability in intergroup contact, but not necessarily awareness of stereotypes.